2011
DOI: 10.2298/ntrp1103218r
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of annual effective radon doses and risk of lung cancer in the residents of district Bhimber, Azad Kashmir, Pakistan

Abstract: Results of indoor radon survey in the dwellings of district Bhimber are presented. Current study is continuation of our preceding studies aiming to setup baseline indoor radon data for the state of Azad Jammu & Kashmir, Pakistan. In this context, 60 representative houses were carefully selected and CN-85 based box type radon detectors were installed in bedrooms and living rooms of each house. The detectors were exposed to indoor radon for 90 days. After etching CN-85 detectors in 6M NaOH at 70°C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
10
1
Order By: Relevance
“…Our average values obtained here is lower than that reported values from Omdurman and Sinnar, Sudan [16], Brazil [47], Iraq [49], and Pakistan [50], higher than the recorded values for Jordan [13], Saudi Arabia [41] and India [46], nearer to the values reported from Al-Hosh (Sudan) [16 ] and USA [44]. …”
Section: Resultscontrasting
confidence: 88%
“…Our average values obtained here is lower than that reported values from Omdurman and Sinnar, Sudan [16], Brazil [47], Iraq [49], and Pakistan [50], higher than the recorded values for Jordan [13], Saudi Arabia [41] and India [46], nearer to the values reported from Al-Hosh (Sudan) [16 ] and USA [44]. …”
Section: Resultscontrasting
confidence: 88%
“…In the three areas of District Bhimber (i.e. Bhimber, Samani and Barnala), radon concentrations and resulting risk of lung cancer for inhabitants were studied by Rafique et al 59 ; giving reported values that varied from 40 AE 9 to 60 AE 7, 29 AE 11 to 58 AE 8 and 29 AE 12 to 66 AE 7 Bqm -3 in Samani, Bhimber and Barnala, respectively. Whereas the reported indoor radon concentration measured by Rafique et al in District Sudhanoti varied from 20 AE 12 to 170 AE 4 Bqm -3 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the petroleum derivatives extract from the core of the earth, therefore, they contain on radioactive nuclides [6]. Human body contains on radioactive nuclides, where there is about 0.0157 g from radioactive isotope in human body and its activity about 0.11μCi [7]. The artificial radioactive sources come from human activities, weapons and nuclear accidents like Chernobyl power station accident in 1986 [8,9].…”
Section: Introductionmentioning
confidence: 99%